The unmanageable consumer - Gabriel, Yiannis, 1952-; Lang, Tim (SAGE, 2015)
Examining the key Western traditions of thinking about and being a consumer, this 20th Anniversary Edition continues to explore 10 consumer models and encourages analysis of contemporary consumerism.